DAMPAK COVID 19 TERHADAP KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR OTOMOTIF DAN ELEKTRONIKA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi Agustina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to analyze empirically the difference between before pandemi Covid 19 and after pandemi Covid 19 to financial performance such as Current ratio, Quick Acid ratio, Cash ratio, DER, ROA, ROE, GPM, NPM, Total Debts to Total Assets and ROCE.Sample of this research are the listed sub sektor otomotif and electronic in Indonesian Stock Exchange from 2019 until 2020.The samples are 16 companies in all sub sektor otomotif and elektronic. This research uses Paired T-Test data analysis. The result of this research shows No one difference between before and after pandemi Covid 19 to financial performance such as Current ratio, Quick Acid ratio, Cash ratio, DER, ROA, ROE, GPM, NPM, Total Debts to Total Assets and ROCE